Application of nanotechnology (nanoparticles) in dark fermentative hydrogen production. (15th January 2019) - Pugazhendhi, Arivalagan; Shobana, Sutha; Nguyen, Dinh Duc; Banu, J. Rajesh; Sivagurunathan, Periyasamy; Chang, Soon Woong; Ponnusamy, Vinoth Kumar; Kumar, Gopalakrishnan
Abstract: An enhanced dark fermentative hydrogen production via the introduction of nanotechnology, utilizing inorganic/organic nanoparticles (NPs) in the membrane of the bioreactors has been renowned these days. Such a nanotechnology includes metal and metal oxides like copper, gold, palladium, silver, iron-iron oxide, nickel-nickel oxide, silica, titanium oxide and carbon nanoparticles (CNTs) respectively have been revealed a noteworthy development in the dark fermentative hydrogen productivity. The pure/mixed cultures can generate dark fermentative hydrogen from biowastes feedstocks with pure sugars derived NPs and the efficiencies in the productivity depends on the nature and concentration of which the NPs employed. In this review, the prospective responsibilities of the inorganic/organic NPs in the enrichment of dark fermentative hydrogen production have been considered for the utilization of the feedstocks like sugars and biowastes materials. Additionally, certain commercial applications in supportive of the integrative approach of inorganic/organic NPs in the case of dark fermentative hydrogen productivity have been discussed. Highlights: Addition of nanomaterials/particles improved the biohydrogen production. Enhanced dark fermentative hydrogen production via inorganic/organic nanoparticles has been accounted. Role of co-addition of inorganic nanoparticles in biohydrogen production explained.